STRENGTH INCREASE METHODS OF THE SIDE FRAME OF THE BOGIE IN THREE–PIECE TRUCKS - Reidemeister, O. H.; Shykunov, O. A. (Science and Transport Progress, 2015)
Purpose. In the paper it is proposed to find methods of structural reinforcement of a side frame of a bogie in areas of stress concentration (the compound zone, the corners of the pedestal jaw opening, etc.), where, as the experience of operation shows, it is possible the emergence of fatigue cracks. It should avoid a significant increase in weight of the structure and does not cause «overflow» areas with a lot of stress from one portion of the structure to another. Methodology. The stresses in the side frame are determined by finite element modeling. Firstly parts of structure that is subject to be strengthened are detected. At the next stage the possible ways of enhancement are developed (wall thickness increase, change of fillet radii, introduction of additional truss plate, etc.). After which according to the results of simulation the effectiveness of each method is evaluated. Amplification of individual sections of the side frame does not always lead to its hardening as a whole (stress decrease in one place often leads to stress increase in the other one). The further procedure is iterative in nature: best-case changes are entered in the design of the frame; weakened areas of construction again are revealed and so on, till to the achievement an acceptable level of safety. Findings. Directional iterative search allows finding a combination of local amplification that increasing significantly the strength of structure. Namely, radius of the transition from the column to the support surface and in the openings between the column and the inclined belt up to 40 and 50 mm are increased respectively; truss plate are added between the upper and lower shelf of Triangel guide and on the inner guide of jaw aperture; technological area of the aperture in the column is reduced by one-third. Due to the proposed stresses combination, voltages in construction were reduced by 41%. Originality. The efficiency of the iterative search procedure of local amplifications combinations in design of the side frame that let significantly increase its strength without a significant increase in weight is presented by scientists. Practical value. Obtained results give the possibility to increase significantly the strength of the side frame in the three-piece truck without any noticeable change in its geometrical and mass characteristics.